Business Retention and Expansion (BRE) Programs: Developing a Business Retention and Expansion Survey - Henry M. Cothran (EDIS)
FE654, a 5-page fact sheeet by Henry M. Cothran, is fourth in a series of 10 publications on establishing Business Retention and Expansion programs. It provides a general overview of the major steps in a process that leads to successful administration of a BRE survey. Includes references. Published by the UF Department of Food and Resource Economics, October 2006.